Synchronization of brain activity associated with eye contact: comparison of face-to-face and online communication - Ren Sato; Hiroki Sato (Scientific Reports)
Abstract Online meetings have become increasingly prevalent, especially during the coronavirus disease 2019 pandemic. Although they offer convenience and effectiveness in various contexts, there is a pertinent question about whether they truly replicate the richness of in-person communication. This study delves into the distinctions between online and face-to-face interactions, with a particular focus on the synchronization of brain activity. Previous research has indicated a connection between synchronization and the quality of communication. Therefore, our hypothesis posits that face-to-face interactions lead to greater brain synchronization compared to online interactions, which often lack certain social cues. To investigate this, we conducted a study using functional near-infrared spectroscopy hyperscanning during an eye-contact task involving 28 male participants organized into 14 pairs. We assessed brain signal synchronization using wavelet coherence analysis. After comparing face-to-face and online conditions, our findings revealed significantly higher synchronization in face-to-face scenarios, particularly within the right temporoparietal region. These results align with the outcomes of other hyperscanning studies and suggest that face-to-face communication elicits a higher level of brain synchronization compared with online communication. In the future, this approach holds promise for evaluating the effectiveness of online meeting tools in achieving a more authentic virtual communication experience.